Dynamic magnetic nanomixers for improved microarray assays by eliminating diffusion limitation - Xiong, Qirong (2021)
Microarrays are widely used in high-throughput analysis of DNA, protein, and small molecules. However, the majority of microarray assays need improved assay speed and sensitivity due to the slow molecular diffusion from bulk solutions to probe surfaces. Here, a new class of magnetic nanomixers in DNA and protein microarray assays is reported to eliminate the diffusion constraint through dynamic mixing. It is demonstrated that the dynamic nanomixers can improve the assay kinetics at least by a factor of 4 and 2 for DNA and protein microarray assays, respectively. By using the dynamic nanomixers, the sensitivities of detecting Escherichia coli O157:H7 DNA and prostate specific antigen increase by more than four-fold. The dynamic mixing also greatly reduces the spot-to-spot variation to below 10% across a broad concentration range, providing more accurate assay results. In comparison with existing methods, this magnetic nanomixer-based approach offers rapid turnaround, improved sensitivity, good accuracy, low cost, simple operation, and excellent compatibility with commercial microarrays.